Uncertainty and the innovative behavior on Keynesian and Neo-schumpeterian approaches - Cavalcante, Thiago (Brazilian Keynesian Review, 2021)
This article analyzes how elements of Keynesian and evolutionary theory - uncertainty, investment and the formation of expectations - prove to be relevant in the decision-making process aimed at theological change of firms. The epistemological method is used to articulate the notion of temporality of expectations and investment decisions in innovation present in both theoretical approaches. Among the results, it is highlighted that the emergence of a new technological paradigm alters the marginal efficiency of previously mobilized capital, as radical innovations alter the quasi-rent linked to prospective adjustments of capital goods. Therefore, investment decisions related to (long term) radical innovations are more susceptible to uncertainty than investment decisions related to (short term) incremental innovations, given the learning process.